Crinivirus replication and host interactions - Kiss, Zsofia A.; Medina, Vicente; Falk, Bryce (Frontiers in Microbiology, 2013)
Criniviruses comprise one of the genera within the family Closteroviridae. Members in this family are restricted to the phloem and rely on whitefly vectors of the genera Bemisia and/or Trialeurodes for plant-to-plant transmission. All criniviruses have bipartite, positive-sense ssRNA genomes, although there is an unconfirmed report of one having a tripartite genome. Lettuce infectious yellows virus (LIYV) is the type species of the genus, the best studied so far of the criniviruses and the first for which a reverse genetics system was available. LIYV RNA 1 encodes for proteins predicted to be involved in replication, and alone is competent for replication in protoplasts. Replication results in accumulation of cytoplasmic vesiculated membranous structures which are characteristic of most studied members of the Closteroviridae. These membranous structures, often referred to as BYV-type vesicles, are likely sites of RNA replication. LIYV RNA 2 is replicated in trans when co-infecting cells with RNA 1, but is temporally delayed relative to RNA1. Efficient RNA 2 replication also is dependent on the RNA 1-encoded RNA binding protein, P34. No LIYV RNA 2-encoded proteins have been shown to affect RNA replication, but at least four, CP, CPm, Hsp70h, and p59 are virion structural components and CPm is a determinant of whitefly transmissibility. Roles of other LIYV RNA 2-encoded proteins are largely as yet unknown, but P26 is a non-virion protein that accumulates in cells as characteristic plasmalemma deposits which in plants are localized within phloem parenchyma and companion cells over plasmodesmata connections to sieve elements. The two remaining crinivirus-conserved RNA 2-encoded proteins are P5 and P9. P5 is 39 amino acid protein and is encoded at the 5’ end of RNA 2 as ORF1 and is part of the hallmark closterovirus gene array. The orthologous gene in BYV has been shown to play a role in cell-to-cell movement and indicated to be localized to the endoplasmic re